Structural analysis - Kassimali, Aslam (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2014)
This work teaches the basic concepts and principles of structural analysis using an intuitive approach. It analyses statically determinate and indeterminate beams, trusses, and rigid frames, as well as introducting matrix analysis of structures.
PART I: INTRODUCTION TO STRUCTURAL ANALYSIS AND LOADS.-- 1. Introduction to Structural Analysis.-- 2. Loads on Structures.-- PART II: ANALYSIS OF STATICALLY DETERMINATE STRUCTURES.-- 3. Equilibrium and Support Reactions.-- 4. Plane and Space Trusses.-- 5. Beams and Frames: Shear and Bending Moment.-- 6. Deflections of Beams: Geometric Methods.-- 7. Deflections of Trusses, Beams, and Frames: Work - Energy Methods.--v 8. Influence Lines.-- 9. Application of Influence Lines.-- 10. Analysis of Symmetric Structures -- PART III: ANALYSIS OF STATICALLY INDETERMINATE STRUCTURES.-- 11. Introduction to Statically Indeterminate Structures.-- 12. Approximate Analysis of Rectangular Building Frames.--13. Method of Consistent Deformations - Force Method.-- 14. Influence Lines for Statically Indeterminate Structures.-- 15. Slope-Deflection Method.-- 16. Moment-Distribution Method.-- 17. Introduction to Matrix Structural Analysis.-- Appendix A: Areas and Centroids of Geometric Shapes.-- Appendix B: Review of Matrix Algebra.-- Appendix C: Computer Software.-- Appendix D: Three-Moment Equation.
Includes index.
Keywords: STRUCTURAL ANALYSIS (ENGINEERING)